Innovative approaches to counseling - Collins, Gary R. (Resources for Christian counseling ;, 1986)
The general editor of the Resources for Christian Counseling series discusses the counseling boom sweeping the country and introduces the reader to a range of approaches that are considered "nontraditional" and "innovative.